Penentuan Kriteria Perbuatan Permulaan Pelaksanaan Pada Tindak Pidana Makar di Indonesia - Wahyu Andrie Septyo; Erdianto Effendi; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Makar comes from the word aanslag (Dutch), which according to the literal meaning is an attack or attack. P. A. F. Lamintang has another interpretation of makar or aanslag which means attack or attack with no good intention. While makar according to Article 87 of the Criminal Code: